Pengaruh Workplace Stretching Exercise Terhadap Kebosanan Belajar Dan Kelelahan Belajar Mahasiswa Poltekkes Surakarta - Lis Sarwi Hastuti; Rina Kurnia (Poltekkes Kemenkes Surakarta, 2017)
bstract : Workplace Stretching Exercise, Boredom, Fatique Learning. This study aims to reveal the impact of Workplace Stretching Exercise to boredom and fatique learning of student in campus I health Polytechnic of Surakarta. Sampling collection was done by purposive sampling technique with 86 respondents.The result of paired samples t-test was obtained p value = 0.001 (p<0.005). Conclusions results of this research is there is the influence of Workplace Stretching Exercise to the boredom and fatique learning student in campus I Health Polytechnic of Surakarta.